An inhibitor of oxidative phosphorylation exploits cancer vulnerability. (July 2018) - Molina, Jennifer; Sun, Yuting; Protopopova, Marina; Gera, Sonal; Bandi, Madhavi; Bristow, Christopher; McAfoos, Timothy; Morlacchi, Pietro; Ackroyd, Jeffrey; Agip, Ahmed-Noor; Al-Atrash, Gheath; Asara, John; et al.
Abstract Metabolic reprograming is an emerging hallmark of tumor biology and an actively pursued opportunity in discovery of oncology drugs. Extensive efforts have focused on therapeutic targeting of glycolysis, whereas drugging mitochondrial oxidative phosphorylation (OXPHOS) has remained largely unexplored, partly owing to an incomplete understanding of tumor contexts in which OXPHOS is essential. Here, we report the discovery of IACS-010759, a clinical-grade small-molecule inhibitor of complex I of the mitochondrial electron transport chain. Treatment with IACS-010759 robustly inhibited proliferation and induced apoptosis in models of brain cancer and acute myeloid leukemia (AML) reliant on OXPHOS, likely owing to a combination of energy depletion and reduced aspartate production that leads to impaired nucleotide biosynthesis. In models of brain cancer and AML, tumor growth was potently inhibited in vivo following IACS-010759 treatment at well-tolerated doses. IACS-010759 is currently being evaluated in phase 1 clinical trials in relapsed/refractory AML and solid tumors. A new inhibitor targeting the mitochondrial complex I shows antitumor activity in preclinical models of acute myeloid leukemia and glioblastoma relying on oxidative phosphorylation.